(untitled) (Altre Modernità, 2018)
Jaime Chabaud, Noche y niebla (Un grito o 43) (México, Amigos Promotores del Teatro/Secretaría de Cultura, 2017, 165 pp. ISBN 978-607-745-625-4) por Ana Sagi-Vela González